2008
DOI: 10.1128/iai.00282-08
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Demonstration and Quantification of Intracellular Bacillus anthracis in Lung Epithelial Cells

Abstract: Inhalational anthrax is initiated by the entry of Bacillus anthracis spores into the lung. A critical early event in the establishment of an infection is the dissemination of spores from the lung. Using in vitro cell culture assays, we previously demonstrated that B. anthracis spores are capable of entering into epithelial cells of the lung and crossing a barrier of lung epithelial cells without apparent disruption of the barrier integrity, suggesting a novel portal for spores to disseminate from the lung. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 34 publications
4
45
1
Order By: Relevance
“…These studies have brought to light data which suggest that a reassessment of a number of the Trojan horse model's central tenets, as they were originally defined, is needed. It was shown in vitro that epithelial cells and fibroblasts can engulf and transcytose spores and vegetative bacilli through cell monolayers without disrupting barrier integrity (63,64,72). These data raised questions as to whether phagocytes are the sole cell type that can act as Trojan horses and thus whether phagocytes are an absolute necessity for spores to transit from the lumena of the lungs.…”
Section: Redefining the Trojan Horsementioning
confidence: 95%
“…These studies have brought to light data which suggest that a reassessment of a number of the Trojan horse model's central tenets, as they were originally defined, is needed. It was shown in vitro that epithelial cells and fibroblasts can engulf and transcytose spores and vegetative bacilli through cell monolayers without disrupting barrier integrity (63,64,72). These data raised questions as to whether phagocytes are the sole cell type that can act as Trojan horses and thus whether phagocytes are an absolute necessity for spores to transit from the lumena of the lungs.…”
Section: Redefining the Trojan Horsementioning
confidence: 95%
“…Spores in the lung are phagocytosed by alveolar macrophages or dendritic cells, which initiate the processes leading to pulmonary anthrax (120,122,123). For pulmonary infections, it has also been shown that B. anthracis spores are capable of entering epithelial cells of the lung and crossing this cell layer without apparent disruption of the barrier integrity (124,125). The gastrointestinal form of anthrax ensues when spores are ingested and migrate to the intestinal tract, where they pass across the gut epithelial cell layer without germination.…”
Section: Functions Of the Exosporium In An Infected Hostmentioning
confidence: 99%
“…An alternative model for phagocyte independent dissemination is that the spores and vegetative bacilli can be internalized by epithelial cells directly [62,271,[278][279][280][281]. These studies are supported by in vitro and in vivo studies that demonstrate that the spores are able to adhere, invade, and transcytose through the epithelial layer [271,279,280].…”
Section: Investigations Of B Anthracis Infections With Bioluminescensupporting
confidence: 54%
“…These studies are supported by in vitro and in vivo studies that demonstrate that the spores are able to adhere, invade, and transcytose through the epithelial layer [271,279,280]. Additionally, B. anthracis spores are unique from related Bacillus spores in that they can reside in the lung for long periods of time [278].…”
Section: Investigations Of B Anthracis Infections With Bioluminescenmentioning
confidence: 53%
See 1 more Smart Citation